Analisis Produksi dan Pendapatan Usahatani Padi Pada Kelompok Tani di Desa Bonder - Amalina, Nur; Utomo, Danang Prio (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2025)
This research aims to 1) To determine the partial influence of production factors (Seeds, Fertilizer, Labor and Land Area) on rice production in farming in the Bonder Village farming group, 2) to determine the production results and income from rice farming in the farming group in Bonder Village. The research method uses a quantitative approach by determining the number of respondents using the Slovin formula. Data analysis was carried out using the Cobb-Douglas production function to determine the influence of production factors on farming results, as well as income analysis using the total revenue (TR) and total cost (TC) approaches. The research results show that the average rice production reaches 5,000 kg per hectare, while the average rice farming income is IDR. 26,000,000 per hectare. Simultaneous testing of production factors produces a value of Fcount = 5684.973 with a significance level of 0.000, which means that the production factors together have a significant effect on rice production in Bonder Village. Income analysis shows that rice farming is still worth pursuing because it can provide quite high profits for farmers. Thus, it can be concluded that efficiency in the use of production factors contributes significantly to increasing production and farmer income.